I, Michael Bennett [large type] - Patterson, James, 1947- (Patterson, James, 1947- Detective Michael Bennett thriller., 2012)
Detective Michael Bennett takes his family to upstate New York in an effort to escape a lawless crime wave erupting in Manhattan, only to find himself immersed in another nightmare, one that endangers his relationship with his wife.